1998
DOI: 10.1002/(sici)1097-0185(199809)252:1<17::aid-ar3>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure of male rats to estradiol benzoate causes rete testis dilation and backflow impairment of spermatogenesis

Abstract: Estrogens administered to perinatal rodents cause spermatogenesis impairment; this study was undertaken to determine the mechanisms by which estrogens exert this effect. Neonatal male Wistar rats received estradiol benzoate (either 0.5 mg/5g BW or 1 mg/5g BW) and were killed at days 10, 22, 33, 45, and 60. Controls received vehicle. In tubule cross-sections of transverse sections of the right testes, 1) tubular diameter (TD) and seminiferous epithelium height (SEH) were measured, 2) normal and impaired spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The increased levels of LH together with decreased levels of serum testosterone are indicative of decreased steroidogenic ability of the testes of the mice transplacentally exposed to progesterone. Earlier reports also indicate that neonatal exposure of male rats to DES resulted in suppression of androgen action and also abnormalities of the male reproductive tract (Arai et al 1983, Newbold & McLachlan 1985, Marselos & Tomatis 1992, Aceitero et al 1998, Fisher et al 1998, Khan et al 1998, Sharpe et al 1998, McKinnell et al 2001.…”
Section: Discussionmentioning
confidence: 96%
“…The increased levels of LH together with decreased levels of serum testosterone are indicative of decreased steroidogenic ability of the testes of the mice transplacentally exposed to progesterone. Earlier reports also indicate that neonatal exposure of male rats to DES resulted in suppression of androgen action and also abnormalities of the male reproductive tract (Arai et al 1983, Newbold & McLachlan 1985, Marselos & Tomatis 1992, Aceitero et al 1998, Fisher et al 1998, Khan et al 1998, Sharpe et al 1998, McKinnell et al 2001.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that several synthetic and natural chemicals through either maternal or neonatal exposure induced developmental disorder of the male and female offspring in rats [1,9,15,24,25,41]. However, the effect on the male and female reproductive organs of the offspring maternally exposed to BP was not yet reported and poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Administration or deprivation of oestrogen, both during development and in the adult, has been shown to cause structural and functional changes in the male reproductive tract, including infertility. Neonatal treatment of male rats with oestrogenic chemicals reduces testicular and epididymal sperm concentration, plasma testosterone (Goyal et al 2003, Sharpe et al 2003, Sertoli cell number (Atanassova et al 2005), alters testicular gene expression (Adachi et al 2004) and causes rete tubule distension and reduced epithelial height in the efferent ducts (Aceitero et al 1998, Fisher et al 1998, 1999. The absence of a functional ER also causes distension of the rete testes, efferent ducts and epididymides, and causes infertility (Lubahn et al 1993, Eddy et al 1996, Hess et al 2000.…”
Section: Introductionmentioning
confidence: 99%